Legal Problem Regarding the Criminal Liability of Internet Provider due to the Distribution of Child Pornography - เกิดสมุทร จักรกรินทร์ (Huachiew Chalermprakiet Law Journal, 2020)
This article is the conclusion of the content of a thesis on the legal problems concerning criminal liability of internet service providers due to the dissemination of child pornography. By studying the concepts of the child protection from pornography related to children. The determination of the acts that are related to the violation of the possession or distribution of child pornography on the internet as well as studying about problem in accordance with laws enforcement. The study according to the operation of any kind of internet service provider by comparing with the determination of the legal liability of Internet service providers in the United States, England and the Federal Republic of Germany to determine the fair measure for internet service providers for prevention and suppression of child pornography dissemination on the appropriate internet network in Thailand. From the study of the essential laws such as Penal Code and the Computer Crimes Act, BE 2550 (2007) found that the definition of pornography related to children under the Criminal Code is not consistent with the current social context. Also, the determination of the duty of the internet service provider as an intermediary according to the law affects the rights and freedom of service providers. Due to the Computer Crime Act 2007, Section 15 stipulates liability of service providers without separating the kind of each service. In addition, the Notification of the Ministry of Digital Economy and Society Re: Process of the Notification, Blocking Dissemination and Deletion of Computer Data from Computer System B.E. 2560 (2017) requires that the offenses under the Computer Crime Act 2007, Section 14, the service providers to be jointly liable unless prepare in accordance with the specified measures to be excused in criminal offences, although the service provider has no intention at first time. Therefore, it is an unfair procedure and creates a burden for unreasonable service providers In order to protect the rights and freedoms from the services of the internet service providers. Therefore, the study should determine the guidelines for solving problems by defining the definition of the word Pornography for clarity in the elements of a crime. The Legislation for Internet service providers to specify duty in accordance with the kind of the service in order that the determination of criminal liability is correct and appropriate.